Evaluation of Nutrients in Leaves and Seeds of Calotropis Procera (linn): A Multipurpose Plant - Ogundola, A.F.; Yekeen, T.A.; Arotayo, R.A.; Akintola, A.O.; Ibrahim, A.O.; Adedosu, H.O.; Bello, M.O. (Journal of Pharmacy and Nutrition Sciences, 2021)
Calotropis procera has been widely explored in ethnomedicine to cure several ailments such as leprosy, fever, elephantiasis, menorrhagia, and snakebite. It is also used as a purgative, anthelmintic, anticoagulant, anticancer, antipyretic, analgesic, and carminative. In addition to its traditional use as coagulants, the leaves and seeds of Calotropis procera could be used in food fortifications to combat nutrient deficiencies as reflected in its bioactive components. The increase in its use might be associated with the level of many bioactive components, which provide nutritional and health benefits. Thus, the leaves and seeds were analyzed for their bioactive components and characterized for nutrient values using the procedures of the Association of Official Analytical Chemists. The chemical analyses results showed that the leaf and the seed contained (g/100 g dry weight) moisture (8.11g, 9.53g), crude protein (26.69g, 14.48g), crude fiber (7.54, 15.73), crude fat (21.70, 6.29), ash (5.32, 3.69) and carbohydrate (30.64, 50.29), respectively. The leaves and seeds contained zinc (1.20, 0.60 mg/100 g), potassium (33.60, 30.30 mg/100 g) and iron (36.90, 12.90 mg/100g), respectively. The fatty acids profile revealed that the leaves and the seed oils contained a low level of saturated palmitic acid (3.01, 7.70 g/100g) and a high level of monounsaturated oleic acid (10.31, 27.90 g/100g) and polyunsaturated acids (11.63, 18.53 g/100g), respectively. It is established that the chemical compounds in the Calotropis procera seeds and leaves could be beneficial for therapeutic and dietary purposes. Thus, it can be accepted that the Calotropis procera plant may be used as medicine and food fortificants.